Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai pada Dinas Pertanian dan Peternakan Kabupaten Kubu Raya - B31112024, Febry Ramadhan Kusuma (Jurnal Manajemen Update, 2016)
Employee performance is the result of the quality and quantity of work achieved by someone employee in performing each job. Performance is owned by employees is an activity that is important to measure the success of an organization in achieving the vision and mission of an organization's. Employee performance itself, one of which can be influenced by factors leader where he had work and discipline which is owned by the employees themselves. This research aims to examine and analyze the effect of leadership and discipline the performance of employees at the Department of Agriculture and Livestock Kubu Raya. Data collected through questionnaires and conducted on 53 employees at the Department of Agriculture and Livestock Kubu Raya. Analysis of the data in this study using IBM SPSS version 16 program assistance. The sampling technique used by the census methods and testing techniques of data used in this study include the validity and reliability test. Classical assumption test and multiple regression analysis, to test and prove the hypothesis of the research. The analysis showed that leadership positive and significant effect on employee performance. Work discipline does not affect significantly the performance of employees. Keywords: Leadership, Work Discipline, Employee Performance